PENGARUH PERBEDAAN METODE PENGERINGAN TERHADAP KANDUNGAN METABOLIT PRIMER RUMPUT LAUT Kappaphycus alvarezii - Waldetrudis Anunut; Ade Yulita Hesti Lukas; Immaria Fransira (Jurnal Aquatik, 2026)
Kappaphycus alvarezii is one of the fishery commodities with high economic value, particularly as a source of carrageenan and primary metabolites. The drying process is a crucial post-harvest stage as it may affect the quality of nutritional content yield. This study aimed to determine the effect of different drying methods on the primary metabolite content of Kappaphycus alvarezii seaweed. The study was designed using a Completely Randomized Design (CRD) with three treatments and three replications, consisting of outdoor hanging drying (P1), solar dome dryer (P2), and outdoor rack drying (P3). The observed parameters included protein, fat, carbohydrate, and carrageenan content, which were analyzed using Analysis of Variance (ANOVA). The results showed that the different drying methods had no significant effect (P > 0.05) on all parameters tested. The highest average protein content was obtained in treatment P1 at 6.23%, the highest fat content in P3 at 1.06%, the highest carbohydrate content in P1 at 40.90%. All three drying methods were able to maintain the nutritional content of the seaweed within a relatively comparable range, suggesting that traditional drying methods can serve as an effective and efficient alternative for seaweed farmers. Keywords: Carrageenan, Kappaphycus alvarezii, Primary metabolites, Drying method, Seaweed.